Comparative notes regarding chinese and japanese immigrants - Rodríguez Pastor, Humberto (2020)
Panoramic view of the complex migratory processes of two groups of migrant Asian workers, Chinese and Japanese, who arrived in Peru in different periods. These were almost continuous, since their presence responded to the need for labor on the coastal haciendas and that they faced coercive forms of demands. Therefore, the leak was similar in both cases.